Effectiveness of Seca Skin Public Relations Marketing through Live Streaming on Tiktok - Alvansa, Mochamad; Manalu, Margareta (Journal of Indonesian Tourism and Policy Studies, 2025)
This study examines the utilization of TikTok's live streaming feature as a public relations marketing strategy in the beauty industry. Using a qualitative descriptive method, the research is grounded in public relations marketing and live streaming theories. Through in-depth interviews, it explores how the beauty brand Seca Skin optimizes this feature to expand market reach, increase sales, and enhance consumer engagement. The findings reveal that Seca Skin successfully meets four key aspects of live-stream selling: Attractiveness, Trustworthiness, Expertise, and Purchase Convenience. These factors contribute to higher audience engagement, strengthened customer loyalty, and more effective purchasing decisions. Moreover, the study highlights that live streaming not only drives sales but also reinforces brand authenticity, credibility, and relatability.